The Impact of Coping With Stressful Events on Negative Affect and Cravings Among Smokers With Mood Disorders. Issue 6 (16th December 2021) - Selva Kumar, Danusha; Nahvi, Shadi; Rivera-Mindt, Monica; Arnsten, Julia; Minami, Haruka
Abstract: Introduction: Smokers with mental illness report elevated levels of stress and negative affect. Craving is often cited as a key precipitant of smoking. Coping with stress has been associated with reduced cravings among smokers attempting to quit. However, the effect of coping with stress on negative affect and craving among smokers with mental illness is not well understood. This study investigated whether coping with stress predicts lower subsequent craving, mediated by reduced negative affect, among socioeconomically disadvantaged smokers with mood disorders. Aims and Methods: This study used ecologically momentary assessment (EMA) data from a randomized controlled trial involving smokers with mood disorders. The final sample included 39 participants. Results: Traditional mediation path analyses showed that coping with stress predicts lower craving ( p = .02) through its impact on negative affect ( p < .001) for the contemporaneous model (ie, when craving was measured at the same report as coping). However, coping with stress did not have a prospective effect on craving (ie, when craving was measured at the next report, up to 12 hours later) ( p = .11). Conclusions: The results suggest that coping with stress reduces craving through negative effect, but only for a limited timeframe. The findings could guide future research on the length of time that the effect of coping lasts and research on interventions to increase coping with stress among smokers with mental illness. Implications: This is the first study to use EMA to demonstrate that coping with stressful events effectively reduces craving through reducing negative affect among smokers with mood disorders. This finding suggests that individuals heavily burdened with stress and negative affect benefit from coping with stress. We utilized within-subject analyses of EMA data which allowed us to understand these effects within an individual near real time. Our sample is hard to reach and ethnoculturally diverse. Findings could guide intervention research on helping smokers with mental illness cope when experiencing stress.